Combination of Warm Compress and Effleurage Massage on the Intensity of Labor Pain in the First Stage of the Active Phase in Maternal Patients at Dr. Hospital. Abdul Rivai, Berau Regency - Bunga, Sari; Masyita, Gita; Meihartati, Tuti; Risnawati, Risnawati (Journal of Midwifery and Nursing, 2024)
This study aimed to determine the effect of a combination of warm compresses and effleurage massage on the intensity of labor pain during the first active phase in maternal patients. This was a pre-experimental study with a one-group pretest and posttest design. The population was all primiparous normal mothers giving birth at dr. Abdul Rivai Hospital Berau, from January to September 2023, numbered 385 people, with an average of 43 people per month, based on the Lameshow formula, which included a sample of 38 people. The instrument used the VAS scale and standard operating procedure (SOP) for a combination of warm compresses and effleurage massage. Data analysis used the paired sample test. The intensity of labor pain during the first active phase before being given a combination of warm compress and effleurage massage had an average value of 7.47. The intensity of labor pain during the first active phase after being given a combination of warm compress and effleurage massage had an average value of 6.26. It showed an effect of the combination of warm compresses and effleurage massage on the intensity of labor pain during the first active phase (p-value = 0.000 < ?: 0.05). This indicates that the combination of warm compresses and effleurage massage affects reducing the intensity of labor pain during the first active phase. It hopes that hospitals can adopt a policy of issuing the standard operating procedure (SOP) for the combination of warm compresses and effleurage massage